Hidradenitis Suppurativa: Where We Are and Where We Are Going - Emanuele Scala; Sara Cacciapuoti; Natalie Garzorz-Stark; Matteo Megna; Claudio Marasca; Peter Seiringer; Thomas Volz; Kilian Eyerich; Gabriella Fabbrocini (Cells, 2021)
Hidradenitis suppurativa (HS) is a chronic inflammatory skin disease primarily affecting apocrine gland-rich areas of the body. It is a multifactorial disease in which genetic and environmental factors play a key role. The primary defect in HS pathophysiology involves follicular occlusion of the folliculopilosebaceous unit, followed by follicular rupture and immune responses. Innate pro-inflammatory cytokines (e.g., IL-1β, and TNF-α); mediators of activated T helper (Th)1 and Th17 cells (e.g., IFN-γ, and IL-17); and effector mechanisms of neutrophilic granulocytes, macrophages, and plasma cells are involved. On the other hand, HS lesions contain anti-inflammatory mediators (e.g., IL-10) and show limited activity of Th22 cells. The inflammatory vicious circle finally results in pain, purulence, tissue destruction, and scarring. HS pathogenesis is still enigmatic, and a valid animal model for HS is currently not available. All these aspects represent a challenge for the development of therapeutic approaches, which are urgently needed for this debilitating disease. Available treatments are limited, mostly off-label, and surgical interventions are often required to achieve remission. In this paper, we provide an overview of the current knowledge surrounding HS, including the diagnosis, pathogenesis, treatments, and existing translational studies.